GE_GERICHTE P/3167/2008 vom 22. April 2015 - GE Cour de justice (2015)
SÉQUESTRE(MESURE PROVISIONNELLE) ; AUTOMOBILE ; LEASING ; CONFISCATION(DROIT PÉNAL) ; PRINCIPE DE LA BONNE FOI ; TIERS | CPP.263; CPP.267; CC.930; CP.70; CC.933